PREDICTIVE POWER OF PARAMETERS INFLUENCING BORROWING BY MSMES (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Small businesses are the lifeline for sustaining  the economy of any nation with their significant  contribution in GDP and employment  generation. The most comprehensive definition  of small business in India has been given by  the Ministry of MSMEs with effect from July,  2020 which classifies MSMEs on the basis  of investment as well as turnover. While the  importance of MSME sector for the economy  is irrefutable, the sector is not free from  problems. A major inhibition to the growth  of the sector is the “access to finance”. It has  been attempted to find out what are some  variables that influence borrowing experience  of MSME borrowers. Borrowing experience  related data were collected from 750 MSMEs  across different districts of Assam with the  help of a schedule. Ordinal regression has  been attempted to develop models to predict  contribution of various demographic and  non-demographic variables to difficulty faced  by the MSME borrowers in obtaining loan  from banks. Factors found to be significant  predictors in identifying various dimensions of  problems faced while borrowing from banks by  MSMEs include inter alia registration status,  age of owner, type of scheme availed, location,  age of the business, etc. Many newly setup  start-up MSMEs can hardly produce any rosy  track record as a pre-condition for institutional  credit accommodation to prove their credit  worthiness; to reduce the risk of lending by  banks and to contain occurrence of NPAs.
Keywords: MSME; Micro; Medium Enterprises; Small Enterprises; Bank; Bank Credit; Entrepreneurial credit